A Report on Micro-invertebrates Associated with Littoral Macrophytes in Kagzipura Lake - G.V. Arak, Satish S. Mokashe, G.K. Kulkarni, A.D. Harkal (Recent Research in Science and Technology, 2011)
The present study deals with micro-invertebrates associated with littoral macrophytes of kagzipura reservoir from January to December 2009.During the present study species of Protozoa, Rotifera, Copepoda, Cladocera and Ostracoda along with Sponges, Bryozoa. Nematodes and Insect larvae are recorded. This study will be helpful to understand the real picture of community structure of limnetic ecosystem.